PENANGANAN PENGUNGSI DI INDONESIA - Rohmad Adi Yulianto (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2016)
that true religious and social solidarity is a supporting factor in the handling ofrefugees in Indonesia. The groups are voicing solidarity keumatan Islam as thecornerstone of refugee protection in Indonesia, either by the strengthening of thecivil society as well as with the approach of religious behavior such as infaq,zakat, sadaqah, sacrificial, and pegumpulannya used to fund the protection andhandling of refugees in Indonesia, even some group voiced that the oppressedMuslim Rohingya refugees to be recognized as part of the citizens of Indonesia,this is all a form of commodification of religion in handling the issue of refugees inIndonesia. Although there are no clear synchronization between communitysolidarity with national interests, even precisely tend paradox, but unconsciouslycommoditization of religion in handling the issue of refugees is preciselystrengthen the role of the international regime to intervene against the nationalinterests of the handling of refugees in Indonesia.